HARMONISASI KELUARGA MELALUI KOMUNIKASI SETARA: MODEL TERAPI KELUARGA VIRGINIA SATIR - Asyhabuddin Asyhabuddin (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2012)
Communication is like two sides of a coin. On the one hand, communication is avital human tool, without which human beings would lose their function as social beings.However, on the other hand, communication is also often a source of contention, conflictand human tragedy. Therefore, it takes appropriate communication patterns, so thatcommunication does not become a boomerang for mankinds.In this context, Virginia Satir’s thought, a therapist for family problems, is worthyto be observed. Satir categorized communicators into five categories, i.e. Placater, Blamer,Computer (Super-Reasonable), Distractor, and Leveler (Interpersonal Communicator). Thefirst four types are communicators who lead to an incongruent communication. All fourwill only lead to conflict within the family as they communicate. The latter is thecongruent communicator: a leveler communicates in an equality setting. Satirrecommended people to use I-Message instead of You-Message communication patterns ifthe are to be levelers.